Penerapan Metode Unified Theory Of Acceptence And Use Of Technology (UTAUT) Dalam Memprediksi Behavioral Intentions Pada Penggunaan E-Commerce Shopee Dikalangan Mahasiswa (Studi Kasus Di Fakultas Tarbiyah Dan Keguruan UIN Ar-Raniry) - Hanifah Oktana Putri; Bustami Yusuf (UNIVERSITAS STEKOM, 2019)
This study aims to determine the effect of performance expectancy, effort expectancy, social influence, facilitating conditions on Behavioral intentions among students Tarbiyah and Teacher Training Faculty (FTK), State Islamic University of Ar-Raniry (UIN Ar-Raniry), in using e-commerce Shopee. The sample used in this study were students who had used e-commerce Shopee. We used the Unified Theory of Acceptance and Use of Technology (UTAUT) methodology in this study by distributing questionnaires both in paper based and by utilizing the google form application. The results of this study indicate that the four factors studied has the positive effects on Behavioral Intention of FTK’s students by 42%.